Economics of grids, clouds, systems, and services : 12th International Conference, GECON 2015, Cluj-Napoca, Romania, September 15-17, 2015. Revised selected papers /: 12th International Conference, GECON 2015, Cluj-Napoca, Romania, September 15-17, 2015. Revised selected papers. (2016) - Unknown
No abstract available